Mapping of Research Publications Concerning Disabilities and Entrepreneurs as Scientific Communication Activities - Hanny Hafiar; Priyo Subekti; Yanti Setianti; Nurul Asiah (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2021)
Limited availability of employment opportunities, making some with disabilities intend to become entrepreneurs. There are a number of research results related to disability and entrepreneurship that have been published and indexed on the Garuda portal. The publication of research results is one of the scientific communication activities. This research aims to map a number of these studies. The research method used is descriptive quantitative. Based on the results of the analysis, it is known that research related to disabilities and entrepreneurship which is published in national journals and indexed on the Garuda portal, the majority of the research content makes the disability community the subject of its study, is followed by disabled entrepreneurs and students with disabilities and makes people with disabilities, in general, the subject of their studies. followed by hearing, physical, visual and intellectual disabilities. Furthermore, there are four clusters of keywords related to the results of disability and entrepreneurial research. The first cluster of entrepreneurs is associated with training, education, ability, motivation, and finance. The second cluster of entrepreneurship is associated with skills, vocational, character, independence, and marketing. The third cluster, entrepreneurship, is associated with mentoring, empowerment, business, and community. The fourth cluster connects entrepreneurship with, welfare, accessibility, economy, and entrepreneurs.Keywords: Scientific communication, entrepreneurship, disability, research trends, concepts ABSTRAKKeterbatasan lapangan kerja, membuat sebagian disabilitas memiliki harapan untuk dapat menjadi wirausahawan. Terdapat sejumlah hasil riset terkait disabilitas dan wirausaha yang sudah dipublikasikan dan terindeks di portal Garuda sebagai salah satu aktivitas komunikasi ilmiah. Oleh karena itu riset ini bertujuan untuk melakukan pemetaan atas sejumlah riset tersebut. Metode yang digunakan adalah deskriptif kuantitatif. Berdasarkan hasil analisis dan pembahasan, diketahui bahwa riset terkait disabilitas dan wirausaha yang dipublikasikan dalam jurnal nasional dan terindeks di portal garuda, mayoritas dari isi riset menjadikan komunitas disabilitas sebagai subjek kajiannya, diikuti oleh wirausahawan disabilitas dan siswa disabilitas, serta menjadikan penyandang disabilitas secara umum sebagai subjek kajiannya, diikuti oleh disabilitas pendengaran, fisik, penglihatan dan intelektual. Selanjutnya terdapat empat klaster kata kunci terkait hasil riset disabilitas dan wirausaha. Klaster pertama wirausaha dikaitkan dengan pelatihan, pendidikan, kemampuan, motivasi, dan keuangan. Klaster kedua wirausaha dikaitkan dengan keterampilan, vokasional, karakter, mandiri dan pemasaran. Klaster ketiga, wirausaha dikaitkan dengan pendampingan, pemberdayaan, usaha dan komunitas. Adapun klaster keempat menghubungkan wirausaha dengan, kesejahteraan, aksesibilitas, ekonomi dan pengusaha.Kata Kunci: Komunikasi ilmiah, wirausaha, disabilitas, tren riset, konsep